2020
DOI: 10.1177/0272684x20974214
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient Safety Education on Undergraduate Nursing Students’ Patient Safety Competencies

Abstract: Patient safety is influenced by a set of factors in various levels of the healthcare system. One of the factors affecting patient safety is safety competencies of the nursing students. The current study aimed to evaluate the effect of patient safety education on patient safety competencies of the nursing students. This quasi-experimental study was conducted with a pretest-posttest deign. The levels of patient safety competencies of 50 nursing students were investigated in a nursing school affiliated to large u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 21 publications
7
60
1
Order By: Relevance
“…A positive relationship between patient safety competency and safety climate perception (Hwang, 2015) and psychological safety (Han & Roh, 2020) has also been reported. A quasi-experimental study showed that the educational intervention was partially effective in improving the patient safety competencies of the nursing students (Torkaman et al, 2020).…”
Section: Although Modern Nursing Inmentioning
confidence: 99%
“…A positive relationship between patient safety competency and safety climate perception (Hwang, 2015) and psychological safety (Han & Roh, 2020) has also been reported. A quasi-experimental study showed that the educational intervention was partially effective in improving the patient safety competencies of the nursing students (Torkaman et al, 2020).…”
Section: Although Modern Nursing Inmentioning
confidence: 99%
“…Patient safety is defined as the prevention of harm to patients and has long been a topic of discussion around the world (Lee et al, 2016). According to a growing body of evidence, improving patient safety competency and reforming health professionals' curriculum are happening slowly in the health professions (Torkaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Improving patient safety competency through education and training has been validated for over a decade by studies done in this field. Incorporating patient safety education into undergraduate nursing curriculum and assessing patient safety competency properly are the initial steps toward enhancing patient safety in clinical settings (Torkaman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The subjects of most previous studies on patient safety educational programs were medical students [ 13 , 14 , 15 ], nursing students [ 16 , 17 ], and healthcare providers including doctors and nurses [ 18 , 19 , 20 ]. In particular, research was conducted on a group of nurses who were acutely aware of various issues related to patient safety in the medical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Inpatients who watched PINK videos increased their comfort in participating in patient safety activities [ 21 ], and changed their attitudes and capabilities in patient safety. As such, patient safety education will increase the willingness to participate by inducing improvements in knowledge and awareness and changes in attitudes [ 13 , 14 , 17 , 31 ] The willingness to participate in patient safety refers to the practice of direct health behavior, so it needs to be considered as an important variable to examine the effectiveness of patient safety education.…”
Section: Introductionmentioning
confidence: 99%